RECENT DEVELOPMENTS IN AVD’S AND PUMP INTAKE SYSTEMS –REVIEW PAPER - S. N. Gadekar; Y. A. Asmar; R. A. Fulmamdikar (International Journal of Innovations in Engineering Research and Technology, 2021)
This review paper focuses on the overview of anti-vortexdevices,pumpsumpsystem,intakestructure,andtheir performance,inrecentyears.Theperformancecharacteristic of pumps is developed by the manufacturer under standard conditions.Butinactualpracticebecauseofapumpandtank design, irregularities at suction, and other parameters, the performance of the pump decreases. One of the major parameter which affects pump performance is vortex formation at the inlet of pump intake causing entrainment of air. These setup design parameters are unchangeable but the effect of vortex formation can be controlled with the help of anti-vortex devices. Therefore, it is essential to study and identify vortex formation in a pump sump system with and without AVD’s. In this review paper, we will be focusing on vortex formation in the pump sump system and its effect on the pump system. Also in addition currently used methods to control vortex/swirl. This review could be useful for studying vortices and anti-vortex devices in the field of pump sump systems for futureuse.